The Effect of Project Based Learning Model (PjBL) in Student Civics Kognitive Learning Results in Basic Schools - Muchtar, Farah; Srie Mulyani; Tiara Yogiarni (Amandemen: Journal of Learning, Teaching and Educational Studies, 2024)
The background of this study is that it is still often found that students during learning activities look unprepared to receive material and many of them are still less interested in Civics lessons, resulting in learning activities not running properly which makes the learning outcomes obtained by students less than optimal. The purpose of this study was to determine the improvement of cognitive learning outcomes of Civics students who get learning treatment using project-based learning (PjBL) learning model and tofind out how the effect of project-based learning (PjBL) learning model on cognitive learning outcomes of Civics students in elementary school. This study used a quasi-experimental type using a sample of fifth grade elementary school students as many as 21 students from the experimental class and 21 students from the control class. The project-based learning (PjBL) model treatment was given to the experimental class while the control class received the STAD cooperative model treatment. The test instrument used in this study was in the form of multiple choice, to measure the ability of the student learning outcomes studied. The results in this study were seen from the average score obtained by students during the pretest before getting treatment in the experimental class of 68.10, then when the posttest was carried out, the average score of students increased to 87.17. Then in the calculation of the regression test of the pretest and posttest data, the value of Fcount > Ftable or 66.424> 4.38 means that H0 is rejected. Thus it can be concluded that the cognitive learning outcomes of Civics students in the experimental class have increased after getting the project-based learning (PjBL) model treatment and there is a great influence on the use of the project-based learning (PjBL) model on the cognitive learning outcomes of Civics students in the experimental class.